LINGUISTIC AND CULTURAL CHARACTERISTICS OF STEREOTYPES IN LITERARY TEXTS AND THEIR ANALYSIS (World Bulletin of Social Sciences, 2025)
Stereotypes are culturalling uoculturology patterns that permeate our world today. Through these patterns, individuals try to adapt to and assimilate into certain cultures. At the same time, stereotypes change and are updated over time, and as generations change, national stereotypes also change. The specific features of national stereotypes in the analyzed work “The Great Empire”, as well as the differences between historical stereotypes and their modern versions, are deeply considered.
Keywords: stereotype; linguoculturology; global and national stereotypes